Obsession in death - Robb, J. D. (New York, N.Y. G.P. Puttnam's Sons, 2015)
NYPSD lieutenant Eve Dallas must contend with an admirer who proves his devotion by killing repeatedly.
Eve Dallas and her billionaire husband are getting accustomed to being objects of attention, of gossip, of speculation. But when Eve becomes the object of one person's obsession... someone who believes the two of them have a special relationship... who would kill for her... Eve knows that underneath the worship and admiration, a terrible threat lies in wait.
Keywords: Dallas, Eve (Fictitious character); Policewomen -- New York (State) -- New York; Murder -- Investigation; New York (State) -- New York; Mystery fiction; Fiction